Polygamous Marriages in Indonesia and Their Impacts on Women’s Access to Income and Property - Nina Nurmila (Al-Jami'ah: Journal of Islamic Studies, 2016)
Most studies on polygamy mainly focus on the male normative interpretation of the Quran. This paper, however, will focus on the practices of polygamy. It will mainly explore whether the practices of polygamy are legal or illegal (unregistered for not following the procedure and requirements stated in the 1974 Marriage Law). This paper argues that most polygamous marriages in Indonesia are illegal. This practice can be considered a form of resistance to the Law which requires a husband to ask the permission from the Religious Court before entering polygamous marriages. This paper will also elaborate various living arrangements of legal and illegal polygamous marriages with various consequences on maintenance and property ownership among wives. [Kebanyakan studi tentang poligami berfokus pada interpretasi laki-laki terhadap al-Quran yang bersifat normatif. Akan tetapi, artikel ini akan berfokus pada praktik poligami. Artikel ini terutama akan menerangkan apakah praktik poligami itu legal atau tidak legal (tidak dicatatkan karena tidak mengikuti aturan yang ditetapkan dalam Undang-Undang Perkawinan/UUP 1974). Artikel ini berargumen bahwa kebanyakan perkawinan poligami itu dipraktikan secara illegal. Praktik ini merupakan bentuk dari penentangan terhadap UUP yang mengharuskan seorang suami memohon izin terlebih dahulu kepada Pengadilan Agama sebelum berpoligami. Makalah ini juga akan menjelaskan berbagai pengaturan hidup dalam perkawinan poligami baik yang legal ataupun yang tidak legal dengan berbagai konsekuensinya terhadap nafkah dan kepemilikan harta di antara para istri.]